Pengaruh Leverage, Pertumbuhan Penjualan, Ukuran Perusahaan, Dan Sustainability Reporting Terhadap Nilai Perusahaan - Ikadianti, Nabila; Tumirin (UMSurabaya Publishing, 2024)
The purpose of this study is to estimate the impact of leverage, sales growth, firm size, and sustainability reporting on firm value in IDX-listed businesses in 2022. This study employs a quantitative approach, utilizing secondary data in the form of comprehensive business financial records and a sustainability report. This study's sample consisted of 85 final sample firms selected using a purposive selection approach. The data was analyzed using multiple linear regression with the SPSS 22 program. The findings indicate that a sustainability report has an influence on business value, but leverage, sales growth, and firm size have no effect. The findings of this study are meant as a guideline for making investment decisions connected to business value and may be used as a reference for other parties that desire to explore relevant issues in the future.